We'll always have summer : a Summer novel - Han, Jenny (Han, Jenny. Summer I turned pretty, 2011)
The summer after her first year of college, Isobel "Belly" Conklin is faced with a choice between Jeremiah and Conrad Fisher, brothers she has always loved, when Jeremiah proposes marriage and Conrad confesses that he still loves her.